Análisis de las precipitaciones en Colombia, pronóstico y tendencias - Gallo Centeno, Tatiana María (Universidad Antonio Nariño, 2021)
The objective of this document is to build downscaling models through the regression of principal components and thus be able to carry out a simulation of precipitation in Colombia during a period from 1981 - 2011 and to carry out climate projections in a period between 2011 - 2070., with the application of the previous SD statistical scale.